Websites and social networks of communes in Slovakia: development and current state - Bačík, Vladimír; Klobučník, Michal (Bulletin of Geography. Socio-economic Series, 2021)
One of the main features of today’s information society is the availability of data of various kinds provided by various companies and organizations. In the following paper, we focus on evaluating the dynamics of development and the current state of existence of web pages of communes in Slovakia, which represent a database of their activities and serve as the main communication channel between citizens and self-government representatives. Another important channel is social networks, which are still enjoying huge popularity among internet users. On the basis of the results of an online questionnaire that involved almost 60% of the addressed self-governments, we will point out the adaptation of self-governments to the use of social networks. An important task of such research is the distribution of the obtained results to end users as well. This is achieved through an example of a description of basic technical and functional specifications by using the web page created by the authors of the contribution. This web page has the ambition of becoming a sort of central access point for all those interested in information about communes in Slovakia. By means of standard tabular, but also interactive graphic and map outputs, it gives an idea of selected indicators of self-governments in a user-friendly form, thus helping to increase client awareness of this specific issue.